Different MDSC Activity of G-CSF/Dexamethasone Mobilized Neutrophils: Benefits to the Patient? - Aarts, Cathelijn E. M.; Hiemstra, Ida H.; Furumaya, Charita; van Bruggen, Robin; Kuijpers, Taco W. (Frontiers in Oncology, 2020)
Human neutrophils exert a well-known role as efficient effector cells to kill pathogenic micro-organisms. Apart from their role in innate immunity, neutrophils also have the capacity to suppress T cell-mediated immune responses as so-called granulocyte-myeloid-derived suppressor cells (g-MDSCs), impacting the clinical outcome of various disease settings such as cancer. Patients undergoing chemotherapy because of an underlying malignancy can develop prolonged bone marrow suppression and are prone to serious infections because of severe neutropenia. Concentrates of granulocytes for transfusion (GTX) constitute a therapeutic tool and rescue treatment to fight off these serious bacterial and fungal infections when antimicrobial therapy is ineffective. GTX neutrophils are mobilized by overnight G-CSF and/or Dexamethasone stimulation of healthy donors. Although the phenotype of these mobilized neutrophils differs from the circulating neutrophils under normal conditions, their anti-microbial function is still intact. In contrast to the unaltered antimicrobial effector functions, G-CSF/Dexamethasone-mobilized neutrophils were found to lack suppression of the T cell proliferation, whereas G-CSF-mobilized or Dexamethasone-mobilized neutrophils could still suppress the T cell proliferation upon cell activation equally well as control neutrophils. Although the mechanism of how G-CSF/Dex mobilization may silence the g-MDSC activity of neutrophils without downregulating the antimicrobial activity is presently unclear, their combined use in patients in the treatment of underlying malignancies may be beneficial—irrespective of the number of circulating neutrophils. These findings also indicate that MDSC activity does not fully overlap with the antimicrobial activity of human neutrophils and offers the opportunity to elucidate the feature(s) unique to their T-cell suppressive activity.